Incentives and Performance Governance of Research Organizations - Welpe, Isabell M.; Wollersheim, Jutta; Ringelhan, Stefanie; Osterloh, Margit; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book contributes to the current discussion in society, politics and higher education on innovation capacity and the financial and non-financial incentives for researchers. The expert contributions in the book deal with implementation of incentive systems at higher education institutions in order to foster innovation. On the other hand, the book also discusses the extent to which governance structures from economy can be transferred to universities and how scientific performance can be measured and evaluated. This book is essential for decision-makers in knowledge-intensive organizations and higher-educational institutions dealing with the topic of performance management.
Performance Management -- Performance Measurement -- Incentives: Monetary or Non-Monetary? Extrinsic or Intrinsic?- Innovation and Creativity: Fostering and Impeding Conditions -- Innovative Approaches to Research Evaluation -- What Research Organizations Can Learn From Knowledge-Intensive Business -- Applied Contributions, Country and Case Studies -- Incentives and Performance: What We Can Learn From a Fairy Tale.
Keywords: Business; Personnel management; Management; Industrial management; Business ethics; Educational policy; ducation and state; Business and Management; Human Resource Management; Innovation/Technology Management; Educational Policy and Politics; Business Ethics; Electronic books